Field notes contributed by Raymond L. Cummins, spring 1985 - Cummins, Raymond L.et al (1985)
In his field notes, Cummins lists various bird sighted in southern, predominately around Lake Rathbun, and notes a low warbler migration. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed